Desenvolvendo competências leitoras : uma proposta didática à luz da semiótica discursiva - Souza, Emili Coimbra de (2023)
The following thesis is related to the teaching of reading based on the approach of syncretic texts (cartoons, reports and advertisements) – more specifically considering the contribution of multisemiotic textual genres as producers of meanings in the improvement of students' reading skills. It is an action-research, developed in the form of a didactic proposal (DP) elaborated according to a class of 23 students in the second year of high school class at a Military Police School in the Southern Paraná. The thesis we advocate is that a work with syncretic textual genres based on studies of discursive semiotics can contribute to broaden the reading comprehension of subjects, enabling them to perceive explicit and implicit elements involved in the construction of meanings in texts. Thus, the overall purpose of the study was to improve reading skills in the light of precepts of discursive semiotics with 23 high school students, checking out the validity of this process in improving the reading comprehension of texts. The specific purposes of this work are: to achieve methodologies for approaching different texts in the classroom, adapting theoretical aspects to reading teaching practices; develop a practical work proposal, based on studies of discursive semiotics; expand the students' perception regarding the identification of marks in the text which help in the process of understanding their meanings; emphasize the importance of considering non-verbal elements for the construction of meaning in texts; contribute to a better understanding and comprehension of texts circulating in the school environment and also in the social environment of students. The main theorists searched for the theoretical approach to reading and improving reading skills were Bakhtin (2011), Barros (2003), Kleiman (2013), Solé (1998), Freire (2008). Statements on the discursive semiotics, its theoretical-methodological principles for reading comprehension of syncretic texts, content plan and expression plan in the process of producing meanings in texts, syncretism and the relevance of verbal and non-verbal elements related to text comprehension were based on the thoughts of Greimas (1975; 1976, 1977; 2012; 2017), Barros (2001; 2002), Fiorin (1994; 1999; 2002; 2006; 2008; 2009; 2016), Floch (1986), Gomes (2009, 2014) and Teixeira (2004; 2008; 2009). During the application of the PD activities, three textual genres were covered: cartoon, report and advertisement. The exploration of the integral parts of these texts was based on principles of semiotics, exploring elements of the expression and content levels. The development of the PD allowed the researcher to better monitor and analyze the actions made during the application of the proposed activities, together with the research participants and the object of study, characterizing this research as exploratory, participatory action research. To verify whether the developed proposal contributed to the development of reading skills, we analyzed the answers given by the students (23 students in the class) to the activities proposed throughout the process and, in particular, we compared the answers given to the activities at the beginning of the application of the PD with the data at the end of the PD. The results obtained in this scientific investigation showed that the application of bases of semiotics when working with students in the teaching and learning process contributes to the improvement of students' reading skills. At the end of the proposal, the students in the participating class demonstrated greater ease in identifying and recognizing elements of the content and expression plans that allow a more critical and reflective reading, such as the different points of view advocated, the figurative and thematic elements that allow building paths of comprehension, as well as the role of non-verbal elements in the production of meanings. However, as learning is always in constant development, there is a need to continue the study of specific points belonging to the levels of analysis - recognition of terms from the same semantic field, proposed/operated transformations in the text, as well as the effects of meaning arising from the choices of verbal elements (linguistic choices, mainly in journalistic texts) – in activities of reading comprehension of syncretic texts.